Detection and Quantification Methods for Viable but Non-culturable (VBNC) Cells in Process Wash Water of Fresh-Cut Produce: Industrial Validation - Truchado, Pilar; Gil, Maria I.; Larrosa, Mar; Allende, Ana (Frontiers in Microbiology, 2020)
The significance of viable but non cultivable (VBNC) cells in the food industry is not well-known, mainly because of the lack of suitable detection methodologies. The study aimed at the optimization of the methodology to differentiate dead and VBCN cells of L. monocytogenes in process wash water (PWW) from the fresh-cut industry. Different methodologies were examined including (i) flow cytometry, (ii) viability quantitative polymerase chain reaction (v-qPCR) using an improved version of the propidium monoazide (PMAxx) dye as DNA amplificatory inhibitor, and (iii) v-qPCR combined PMAxx and ethidium monoazide (EMA). The results obtained showed that the flow cytometry although recommended was not a suitable methodology to differentiate between dead and VBNC cells in PWW, probably because of the complex composition of the water, causing interferences and leading to an overestimation of the dead cells. When v-qPCR was used combining qPCR and different DNA amplificatory inhibitors under different conditions (e.g. type of dye, concentration and incubation time and temperature), the combination of the two dyes, PMAxx and EMA, gave the best resolution to differentiate between dead and VBNC bacteria. The optimized conditions achieved included the use of 75 µM PMAxx and 10 µM EMA incubated at 40 ºC for 40 min followed by a 15 min-light exposure. The selected methodology was validated in an industrial processing line where shredded lettuce wash washed with 10 mg/L of chlorine. The analysis of PWW samples allowed the differentiation of dead and VBCN cells. These results evidenced the initial hypothesis about the capacity of chlorine to induce the VBNC state of foodborne pathogens present in PWW. However, based on the lab-scale studies, a slight overestimation on the percentage of VBNC was observed, meaning that this methodology cannot completely discriminate the dead cells. More studies are needed to determine the significance of VBNC cells in case of potential cross-contamination of fresh produce during washing.